Evaluasi Waktu Tunggu Pelayanan Obat dengan Menggunakan Sistem Lean Managemen di Instalasi Farmasi Rawat Jalan RS Prima Pekanbaru - Wika Juwita; Didin Saepudin; Rukhiyat Syahidin (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Long waiting times for outpatient pharmacy services remain a major challenge in hospital service quality and patient satisfaction. At the Outpatient Pharmacy Installation of RS Prima Pekanbaru, increasing prescription volumes have not been matched by service capacity, leading to delays that exceed national standards. This study aims to evaluate outpatient pharmacy waiting times using Lean Management principles and queueing theory to identify sources of inefficiency and propose improvement strategies. A qualitative research design supported by quantitative queue analysis was applied. Data were collected through observations, document review, and in-depth interviews with 11 informants, including pharmacists, pharmacy supervisors, hospital management, prescription verifiers, and patients. The results showed an average prescription arrival rate of 1.717 prescriptions per hour, while the service rate was only 0.912 prescriptions per hour, indicating an unstable queue system. The average processing time for one prescription reached 1.09 hours, exceeding the 60-minute standard for compounded medications. Major inefficiencies were identified in the form of overproduction, particularly at the packaging stage, overprocessing due to repeated data entry caused by incomplete implementation of electronic prescriptions, and defects related to administrative and service flow errors. These findings indicate that optimizing workflow, strengthening human resources, and fully integrating digital systems are essential to reducing waiting times and improving pharmacy service performance.